The relationship between the media and advertisement with body image perception among women / Norshatilla Ezanie and Dewi Tajuddin - Ezanie, Norshatilla; Tajuddin, Dewi (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
Research has suggested that exposure to the mass media has affected our perception of things. Previous studies have shown that women tend to internalise messages by the media more often than men, and this has led the industry to target young women as the subject of insecurity manipulation in order to boost the sale of certain products. It has been suggested that exposure to mass media contents depicting a thin body as the ideal shape is linked with body image disturbance among women. A total of 200 Universiti Malaysia Sabah female students aged 18- 30 were randomly selected to participate in this study to test whether the exposure to today's mass media contents and advertisements has affected their perception of their own body image. The results demonstrate a significant impact of thin-ideal images in the media and advertisements on women's body image disturbance.